2019
DOI: 10.2214/ajr.18.20846
|View full text |Cite|
|
Sign up to set email alerts
|

Aspirin Is Associated With Improved Liver Function After Embolization of Hepatocellular Carcinoma

Abstract: OBJECTIVE. The purpose of this study was to assess the mechanism by which aspirin therapy improves survival when combined with transarterial chemoembolization or transarterial embolization (TAE) for hepatocellular carcinoma (HCC). MATERIALS AND METHODS. A retrospective review included 304 patients with HCC who were treated with TAE. The patients were divided into two groups on the basis of whether the patient took aspirin (n = 42) or did not take aspirin (n = 262) at the time of initial TAE. For each patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 18 publications
1
30
0
Order By: Relevance
“…Similar findings have been made in HCC, as clinical studies showed that long-term aspirin usage is associated with a dose-dependent reduction in HCC-risk [100,103,105,106]. It has also been shown that aspirin reduces the risk of liver fibrosis in patients who have been transplanted for hepatitis C [107] and is associated with an improved liver function and survival after chemo-embolization [108,109]. Interestingly, the effect of aspirin is not limited to its anticoagulant function, as aspirin can also directly decrease tumor cell proliferation [110], increase sensitivity to chemotherapeutics [101,111,112], and induce apoptosis [113].…”
Section: Targeting Platelets As a Therapeutic Strategy In Liver DIsupporting
confidence: 55%
“…Similar findings have been made in HCC, as clinical studies showed that long-term aspirin usage is associated with a dose-dependent reduction in HCC-risk [100,103,105,106]. It has also been shown that aspirin reduces the risk of liver fibrosis in patients who have been transplanted for hepatitis C [107] and is associated with an improved liver function and survival after chemo-embolization [108,109]. Interestingly, the effect of aspirin is not limited to its anticoagulant function, as aspirin can also directly decrease tumor cell proliferation [110], increase sensitivity to chemotherapeutics [101,111,112], and induce apoptosis [113].…”
Section: Targeting Platelets As a Therapeutic Strategy In Liver DIsupporting
confidence: 55%
“…inverse relationship reported between antiplatelet therapy and HCC recurrence was further confirmed by liver resection, transarterial embolization (TAE) and sorafenib. [16][17][18] A large retrospective study revealed that use of aspirin/clopidogrel can reduce the risk of HCC recurrence to 27% and the risk of overall mortality to 43% in patients with HBVrelated HCC after liver resection. Moreover, a small-scale cohort study suggested that aspirin administration can improve liver function test results and survival after TACE for HCC but not response or time to progression.…”
mentioning
confidence: 99%
“…Moreover, a small-scale cohort study suggested that aspirin administration can improve liver function test results and survival after TACE for HCC but not response or time to progression. 17 Our study has some strengths, including the secondary analysis of a large, well-characterised HCC population with retrospective clinical data and more than 115.3 months of follow-up. Besides, in this study, a U-shape relationship between ΔPLT and OS of HCC was calculated through restricted cubic spline regression, and the threshold effect of ΔPLT on OS was calculated through a two-piece wise Cox proportional hazards model.…”
mentioning
confidence: 99%
“…In secondary prevention, the inverse relationship between antiplatelet therapy and HCC recurrence was further confirmed by liver resection, transarterial embolisation and sorafenib. [26][27][28] A large retrospective study revealed that aspirin/clopidogrel use reduced the risk of HCC recurrence to 27% and the risk of overall mortality to 43% in patients with HBV-related HCC after liver resection. Additionally, antiplatelet treatment was related to lower recurrence risk in patients younger than 50 years and female patients.…”
Section: Discussionmentioning
confidence: 99%
“…26 Moreover, the evidence from a smallscale cohort study suggests that aspirin use improves liver function test results and survival after TACE for HCC but not response or time to progression. 27 Our study has some strengths, including the secondary analysis of a large, well-characterised HCC population with retrospective clinical data with more than 115.3 months of follow-up. First, we found that a U-shaped relationship between PLT and HCC OS was calculated through restricted cubic spline regression, and the threshold effect was calculated through a two-piecewise Cox proportional hazards model.…”
Section: Discussionmentioning
confidence: 99%